Augmented Reality Based Flashcard Media to Improve Student Learning Outcomes on the Topic Water Cycle V Grade Elementary School - Kadek Kartika Listiani; Wayan Eka Paramartha (Universitas Pendidikan Ganesha, 2025)
The problem of lack of motivation and learning experience that causes a decrease in student learning outcomes. This study aims to develop augmented reality-based flashcard media to improve student learning outcomes on the topic of the water cycle in grade V SD that is valid, practical and effective. The research conducted is a development research (Research & Development) and uses the ADDIE development model. The data collection method used in this research is using questionnaire instruments and objective tests. Data on the results of media validity comes from the assessment of learning material experts and learning media experts. In this study obtained the results of the material expert assessment of 4.87 and 4.91 from the assessment of learning media experts, so that these results have very good qualifications. Data from the practicality of the media comes from the assessment of the practitioner's response and the response of 10 fifth grade students. The percentage result of the practitioner's response is 91% and the student's response is 95.2%, so that the response results can be qualified as very good.The results of the research on augmented reality-based flashcard media to improve student learning outcomes on the topic of the water cycle in grade V elementary school were declared: (1) valid based on the aspects of content, design and learning media, (2) practical based on the perspectives of practitioners and students, (3) effective to improve student learning outcomes on the topic of the fifth grade water cycle as evidenced by the results of the t-test. Based on these results, it can be concluded that flashcard media based on augmented reality is valid, practical and effective in improving student learning outcomes.